Potential of X-ray irradiation for pathogen inactivation in semi-moist pet food and changes in nutritional and physicochemical qualities - Sethukali, A.; Hyun Jung, L.; Dongbin, P.; Hyun-Jun, K.; Azfar, I.; Jae-Kyung, K.; Cheorun, J. (Elsevier, 2025)
The aim of the study was to investigate the effect of X-ray irradiation at different dose levels on semi-moist pet foods. Samples were subjected to X-ray irradiation at 0, 2.5, 5, and 10 kGy, and their microbial, nutritional and physicochemical properties were evaluated for 60 days at 20-day intervals. Among these, samples irradiated at 10 kGy completely sterilized bacterial pathogens and inhibited their growth throughout the storage period. Following this, a dose of 5 kGy showed a better bacterial pathogen reduction. Above 5 kGy irradiated samples exhibited a significant effect on moisture and protein contents. Samples treated with above 5 kGy tended to exhibit a significant decline in water activity, pH, and a* values during the storage period while continuing to exert microbial stability and quality attributes. However, lipid oxidation and protein degra- dation were observed in samples irradiated with above 5 kGy of X-ray during storage. Considering all results, we conclude that about 5 kGy X-ray irradiation could prevent microbial activity while maintaining the maximum losses of nutritional and physicochemical properties of semi-moist pet foods.
Keywords: X-ray irradiation; Semi-moist pet foods; Bacterial pathogen; Nutritional properties; Physicochemical properties